PENERAPAN TQM DALAM PENDIDIKAN AKHLAK - Wiyani, Novan Ardy; Najib, Muhammad; Sholichin, Sholichin (Jurnal Pendidikan Islam, 2016)
This study is proposed to know the steps in implementing Total Quality Management (TQM) to form the character of students in elementary Al Irshad Al Islamiyyah 02 Purwokerto. The research used cualitative-descriptive approach. Data collection techniques used in this research were interviews, observation and documentation. Data were collected through triangulation and analyzed by using inductive data analysis techniques following three steps: namely note taking, organizing and coding. The research result shows that there are five steps taken in implementing TQM to form the character of students in elementary Al Irshad Al Islamiyyah 02 Purwokerto. First, Improving student’s character continuously. Second, establishing quality assurance for the student’s character. Third, changing the culture of schools to shape the character of the students. Fourth, changing school organization to form the character of students. Fifth, establishing the network with guardians of students in shaping the character of students.